Metallo-β-lactamase-producing Pseudomonas aeruginosa in two hospitals from southern Brazil - Wirth,Fernanda W. (2009)
This study determined the prevalence of metallo-β-lactamase (MBL)-producing Pseudomonas aeruginosa in two hospitals located in the Southern part of Brazil and compare the performance of two different phenotypic tests. Thirty-one non-repetitive Pseudomonas aeruginosa isolates from various clinical samples from patients admitted to two hospitals located in Rio Grande do Sul, Brazil (twenty-three from a hospital in Porto Alegre City and eight isolates from a hospital in Vale dos Sinos Region). All strains suggestive of possessing MBLs by phenotypic methods were included in this study. Phenotypic detection of MBLs was carried out simultaneously by using both the MBL Etest® and disk approximation test using 2-mercaptopropionic acid close to a ceftazidime disk. Strains positive were further confirmed using molecular techniques for blaVIM, blaIMP and blaSPM-1. The prevalence of MBLs from samplesof inpatients from the hospital located in Porto Alegre was 30.4% and that of inpatients from Vale dos Sinos hospital was only 3.1%. Only MBL type SPM-1 was detected in these samples by molecular analysis and all were detected by the Etest® MBL strips. The prevalence of P. aeruginosa that produce MBLs can be markedly different in distinct geographical areas, even among different hospitals in the same area. In our study, the EDTA-based method was the only method able to detect all strains harboring the SPM-1 enzyme.